Nursing diagnoses in the hemodynamics sector: an adaptive perspective - Angela Antonia Sartori; Mari Ângela Gaedke; André Carlos Moreira; Murilo dos Santos Graeff (Revista da Escola de Enfermagem da USP, 2018)
ABSTRACT Objective: To identify nursing diagnoses of NANDA-I Taxonomy II in patients treated in the Hemodynamics Sector. Method: A descriptive, cross-sectional study with a quantitative approach conducted in a teaching hospital in the interior of Rio Grande do Sul. Data were collected through a sociodemographic characterization instrument and information regarding the problems of physical-physiological adaptation. Results: 100 patients participated in the study. Defining characteristics, risk factors and related factors were identified through adaptation problems. In all, 28 nursing diagnoses were identified, and 13 were considered for the discussion which presented frequency above 50% and represented the main adaptive problems. Protection, neurological and activity and rest components were the most frequent. Conclusion: The recognition of nursing diagnoses facilitates a connection between the main problems of adaptation and nursing interventions.